The role of cell transplantation in modifying the course of limb girdle muscular dystrophy: a longitudinal 5-year study - Sharma, Alok (Degener Neurol Neuromuscul Dis, 2015)
Limb girdle muscular dystrophy (LGMD), a group of progressive degenerative disorders, causes functional limitation affecting the quality of life. Cell therapy is being widely explored and preliminary studies have shown beneficial effects. Cell therapy induces trophic-factors release, angiogenesis, anti-inflammation, and protein synthesis, which helps in the reparative process at the microcellular level. In this 5-year longitudinal study, the effect of autologous bone marrow mononuclear cells is studied on the natural course of 65 patients with LGMD. Functional Independence Measure and manual muscle testing showed statistically significant improvement, post-cell transplantation. The key finding of this study was demonstration of a plateau phase in the disease progression of the patients. No adverse events were noted. Autologous bone marrow mononuclear cells may be a novel, safe, and effective treatment approach to control the rate of progression of LGMD, thus improving the functional outcomes. Further randomized controlled trials are required.